EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR PESERTA DIDIK - pudholi, Yusup Arya; Wardani, Kusuma; Rizky, Hafiz; Fadhilah, Ridho; Jadid, Badru; Ramadhan, Bintang Aditya; Khairunnisa, Arin (SINERGI : Jurnal Riset Ilmiah, 2025)
This study analyzes the effectiveness of the Problem Based Learning (PBL) model in enhancing students' critical thinking skills and learning outcomes. Using a literature review approach. The analysis shows that PBL consistently improves students’ critical thinking, active learning, and collaborative skills. It also highlights that PBL increases conceptual understanding in science and enhances situational analysis and argumentation skills in social studies. However, the study identifies challenges in implementing PBL, including difficulties in designing authentic problems and managing instructional time. Effective teacher training, especially in scaffolding techniques and problem design, emerges as a key factor in optimizing PBL implementation. Additionally, the integration of digital resources and supportive learning environments significantly contributes to the success of PBL. Therefore, developing teachers' professional competencies and providing adequate infrastructure are crucial strategies to maximize the potential of PBL in fostering 21st-century skills.